2008
DOI: 10.1021/ie800822n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Limonene Epoxidation over PW-Amberlite

Abstract: The kinetics of limonene epoxidation catalyzed by PW-Amberlite under triphasic conditions is described. A mechanistic pathway was postulated, and a heterogeneous kinetic model was derived following pseudostationary-state theory. Using adsorption parameters that were estimated from independent binary adsorption experiments, the resulting kinetic model fitted the experimental data quite well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The concentration of H 2 O 2 in the reaction mixture was determined by cerimetric titration using a Ce­(SO 4 ) 2 standardized aqueous solution . The reaction of the colored cerium­(IV) sulfate to the colorless cerium­(III) sulfate proceeds in the presence of H 2 O 2 to yield sulfuric acid and oxygen as is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of H 2 O 2 in the reaction mixture was determined by cerimetric titration using a Ce­(SO 4 ) 2 standardized aqueous solution . The reaction of the colored cerium­(IV) sulfate to the colorless cerium­(III) sulfate proceeds in the presence of H 2 O 2 to yield sulfuric acid and oxygen as is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…57,58 Other reported methods include colorimetric detection, 59 spectrophotometry, 60,61 a technique using leuco crystal violet, 62 iodometric titration, 27,33,35 and cerimetric titration. 63 This study aims to evaluate the use of magnesium oxide as a highly selective catalyst for the R-(+)-limonene epoxidation using a versatile Payne reaction system toward epoxide and diepoxide, depending on the reaction conditions. Furthermore, kinetic equations based on pseudohomogeneous and heterogeneous models are proposed, and detailed characterizations of the fresh and spent catalysts are presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, aqueous hydrogen peroxide (H 2 O 2 ) has gained promising attention as a sustainable oxidant for alkene epoxidation. [55][56][57][58][59][60][61][62][63][64][65] The use of H 2 O 2 as an oxidant is advantageous as it produces only water, making it a green and eco-friendly process. [66][67][68] Studies on H 2 O 2mediated epoxidation have employed various catalysts containing metals such as molybdenum (Mo), rhenium (Re), titanium (Ti), and tungsten (W).…”
Section: Hydrogen Peroxide (H 2 O 2 )mentioning
confidence: 99%
“…Some simulation and experimental data for typical essential oils such as citrus and turpentine using fractional distillation demonstrated that it is an adequate method to separate and increase the purity of some components. Limonene 1,2‐epoxide recovery from d ‐limonene epoxidation mixture over PW‐Amberlite/H 2 O 2 /acetonitrile was simulated at 95.6 % . Citronella oil fractionation and the experimental purification of d ‐limonene from green mandarin and orange oils under vacuum conditions have been also reported .…”
Section: Introductionmentioning
confidence: 99%